Analisis Tingkat Kerusakan Jalan Perkerasan Lentur Dengan Metode Pavement Condition Index (PCI) Studi Kasus: Jalan Pelabuhan Talang Duku Muaro Jambi - Mariza Sanubari; Fakhrul Rozi Yamali; Ria Zulfiati; Fakhrul Rozi Yamali (Jurnal Civronlit Unbari, 2023)
Road pavement is the main infrastructure in transportation system. The condition of the pavement affects the comfort, security and safety of road users and is a supporting factor for the progress of the economic and social system in an area. This study aims to analyze the type of damage and level of performance in pavement conditions and provide repair solutions based on the 1995 Bina Marga standard method. The PCI method used in this study is an analysis of 3 main factor functions, namely: type of damage, level of damage severity and amount of damage. The result of the PCI method is a numerical index whose value is 0 to 100. Based on the results of research on the Talang Duku Harbor road, Taman Rajo District, Muaro Jambi Regency with a length of 4.7 Km and a width of 6 M, the highest type of damage was found, namely Patches with 65 damage and damage. the lowest is Amblas, Groove, Basin, Cracked Box with 1 damage and the average PCI value of all segments is 57.36%.